Piezosurgery versus rotary instrument in mandibular third molar surgery - Yadav, Deepak; Karki, Bijay; Mishra, Ravish; Kandel, Laxmi; Ali, Shahid (Journal of Chitwan Medical College, 2024)
Background: The purpose of this study is to compare the effect of surgical removal of third molar by using piezosurgery versus rotary instrument in terms of pain, swelling, infection, and trismus along with operative time difference between the procedures. Method: The study was designed as an observational prospective study, and implemented on patients who required surgical removal of impacted mandibular third molar visiting the Department of Oral and Maxillofacial Surgery, UCMS College of Dental Surgery, Bhairahawa, Nepal. Patients were divided into two equal groups, Gr A: Piezosurgery, and Gr B: Rotary instrument. Variables measured were intraoperative time, pain, swelling, mouth opening, and infection on the 1st, 3rd, and 7th postoperative days. A p-value <0.05 was considered statistically significant. Result: Out of 70 patients, 35 in Gr A and 35 in Gr B; the pain was less on all post-operative days in Gr A but the difference was statistically non-significant. The swelling was lesser in all postoperative days in Gr A than in Gr B, and the differences were statistically significant for 3rd, and 7th days. The mean intraoperative duration was 31.4 minutes in Gr A and 23.8 minutes in Gr B, differences were statistically significant. Mouth opening was more in Gr A than in Gr B, on postoperative days and the differences were statistically significant for 3rd, and 7th days. Conclusion: Piezosurgery took a longer time, but had a better outcome in terms of postoperative pain, swelling, and trismus.